(untitled) (Italian Journal of Public Health, 2005)
Human beings, make errors Healthcare Services is a complex industry prone to accidents.The IOM Report [1] points out that some systems are more prone to accidents than others. When a system fails there are often multiple faults. In healthcare,human errors are the greatest contributors to accidents,however when human error is to blame it often depends upon failures within the system.These failures exists in the system before the error occurs, the same as with latent errors which are difficult to identify since they may be hidden in computers or within the various managerial layers. Most of the errors can be prevented by designing systems that make it hard for people to do the wrong thing and easy for people to do the right thing. In healthcare, this means designing processes that are able to ensure that patients are safe from accidental injury. As healthcare and the system that delivers it become more complex, the opportunities for errors abound. The IOM report “To Err is Human” proposes an approach for reducing medical errors and improving patient safety.The environment within which this occurs has a critical influence on quality.This influence may contain two dimensions; the first consists of the domain of quality which includes the practice that is consistent with current medical knowledge. The second dimension consists of forces in the external environment that can drive quality improvement in the delivery system. Although the risk of dying as a result of a medical error, far surpasses the risk of dying in an airline accident, public attention has been more focused on improving safety in the airline industry than in healthcare systems. Because of the absence of standardized nomenclature, it is important to define what an error is and what is an adverse event, the IOM Report defines them in the following way: “An error is the failure of a planned action to be completed as intended or the use of a wrong plan to achieve an aim.” An adverse event is an injury caused by medical management rather than the underlying condition of the patient. An adverse event attributable to error is a “preventable adverse event”.